Development and feasibility of a brief Zero‐time Exercise intervention to reduce sedentary behaviour and enhance physical activity: A pilot trial. (1st March 2019) - Lai, Agnes; Stewart, Sunita; Wan, Alice; Thomas, Carol; Tse, Joyce; Ho, Daniel; Chan, Sophia; Lam, Tai‐Hing
Abstract: A brief intervention using Zero‐time Exercise (ZTEx), a foot‐in‐the‐door approach, was developed to reduce sedentary behaviour and increase physical activity. ZTEx refers to the integration of simple strength‐ and stamina‐enhancing physical activity into daily life, which can be done anytime, anywhere and by anyone. This paper presents the development, feasibility, and preliminary evidence for the effectiveness of this intervention under the Hong Kong Jockey Club FAMILY Project. Needs assessments were conducted with social workers from the Christian Family Services Center(CFSC) and the Social Welfare Department (SWD). This single group prospective ZTEx intervention trial, guided by the Health Action Process Approach, included a 3‐hr core session at baseline and a 1‐hr booster session at 1‐month follow‐up. Fifty‐six participants (social and service‐related workers) from CFSC ( n  = 28) and SWD ( n  = 28) received the intervention and completed the self‐administered questionnaires at baseline. Forty‐nine and 43 participants completed the 1‐month and 3‐month self‐administered questionnaires, respectively. Fifteen participants attended the focus group interviews to share their feedback on ZTEx intervention after implementing their community‐based ZTEx activities. Intention‐to‐treat analysis was conducted with missing data replaced by baseline values. Participants reported significant decreases in sitting time by 27 (2, 52) minutes (mean [95% confidence interval]) and 36 (0.2, 71) minutes on a weekday, increases in physical activity while seated by 0.7 (0.2, 1.4) days and 1.1 (0.6, 1.7) days in a week, and improvements in perceived knowledge, outcome expectancies and plan on doing ZTEx at the 1‐month and 3‐month follow‐up, respectively. Balance and muscle strength significantly improved at the 1‐month follow‐up. The effect ranged from small to large (Cohen's d : 0.27–1.05, all p  < 0.05). The qualitative feedbacks support the quantitative findings. Our findings show early evidence that ZTEx effectively reduced sedentary behaviour and enhanced physical activity and fitness. Further trials on this simple and low‐cost intervention as the first step to promote higher intensity exercise are warranted.